Water is a critical factor in evaluating and assessing microbial colonization and destruction of Angkor sandstone monuments - Liu, Xiaobo; Meng, Han; Wang, Yali; Katayama, Yoko; Gu, Ji-Dong (International biodeterioration & biodegradation, 2018)
Sandstone monuments/temples of the Angkor Empire in the Southeast Asia are important UNESCO World Cultural Heritage of the Khmer Civilization and recorded history for the people today. Majority of these monuments suffer severe deterioration from weathering caused by a combination of physical, chemical and biological forces, including natural and anthropogenic influences. Current knowledge on deterioration of sandstone is not only scattered, but also isolated and restricted by the specialized disciplines/fields of the investigators, resulting in a lack of comprehensive understanding or integrated information on the causes and mechanisms to the damage of these temples/monuments. It is clear that water is the most critical factor, if not the utmost important one over time, affecting the integrity of the sandstone constituents of the overall architecture and also the carvings of bas-relief at many of these temples. Water is important to life and promotes the mobility of solutes, and both microbial and plant growth accelerates the destabilization of the stone structural integrity. Colonization by plants and microbes alters the local environmental conditions allowing dissolution of sandstone and mobility of solutes from and out of the sandstone. When water is not drained effectively from these temples/monuments for an extended period of time, stagnation of water forms a small pool, providing moist and water into sandstone nearby and below for an extended longer period of time. Under evaporation condition, the accumulated solutes in water can be concentrated and also transported into sandstone through initiation of capillary phenomenon to lead to salting effect and attack of the sandstone. Soluble salts in sandstone can be crystallized under further drying conditions to result in defoliation of the outer surface layer from the sandstone structure. With the supply of water, microorganisms can also contribute in a number of ways to the physical and chemical destruction processes involved. Therefore, a holistic approach with water considered must be formulated in investigation of the mechanisms involved and protection measures of Angkor sandstone temples and architecture. •Water availability is a key factor affecting the integrity of sandstone temples in Southeast Asia.•Microbial colonization on surfaces has different effects for protection and destruction at different stage of development.•Solutes and electrolytes are transported into sandstone resulting in defoliation of surface layers.•Both sulfur and ammonia oxidizing microorganisms are active agents contributing to the acid attack of the sandstone.